Penerapan model peer teaching terhadap hasil belajar dribbling dalam pembelajaran bola basket pada kelas VIII SMPN 1 bayan - Yunika Febriyani; Subakti; Siti Rabiatul Adawiyah (Jurnal Pengetahuan dan Pendidikan, 2023)
Based on the results of observations on basketball material learning at SMPN 1 Bayan class VIII, teachers still use conventional learning methods. The observation results show that students' dribbling learning outcomes in basketball learning are still lacking. This can be seen from the learning outcomes of dribbling not achieving classical mastery. This shows that the learning process has not actively involved students, the teacher is still the center of learning, the lack of teaching models or methods in learning is still not developed enough to achieve educational goals. From the results of the research and discussion, the following conclusions can be drawn: The application of peer teaching is able to improve student learning outcomes at SMPN 1 Bayan. Improved student learning outcomes can be seen from the learning outcomes achieved in the implementation of tests in Cycle I and Cycle II. Students who take part in the learning process are 25 students with the number of students who pass the Cognitive test 100%, Affective test 100%, and Psychomotor test 92%.